2013
DOI: 10.1002/eco.1390
|View full text |Cite
|
Sign up to set email alerts
|

Novel ways to assess forested wetland restoration in North Carolina using ecohydrological patterns from reference sites

Abstract: Restoring jurisdictional wetland hydrology does not ensure that the hydrologic conditions of any specific natural forested wetland community are recreated. This is especially problematic for a state like North Carolina, which has roughly two dozen different forested wetland communities. Because forested wetland communities align themselves across edaphic and hydrologic gradients, we suggest exploiting these relationships to guide restoration design and set performance standards. However, methods to compare hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…NMDS ordinations displaying species composition centroids for the cluster analysis assemblages showed more coherent and consistent groupings than equivalent centroids for the sites. This supports the idea that differences in vegetation composition between sites were determined largely by hydrological factors (Johnson et al ). A practical consequence is that the species assemblages derived collectively from the sites should provide a more precise basis for defining reference condition than any derived from individual sites.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…NMDS ordinations displaying species composition centroids for the cluster analysis assemblages showed more coherent and consistent groupings than equivalent centroids for the sites. This supports the idea that differences in vegetation composition between sites were determined largely by hydrological factors (Johnson et al ). A practical consequence is that the species assemblages derived collectively from the sites should provide a more precise basis for defining reference condition than any derived from individual sites.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, higher salinities in the surface layer of soil resulted from evapotranspiration during the dry season and salts leaching from higher areas. Similar diversity in water‐table levels among reference sites has also been reported recently in a study of forested wetland restoration (Johnson et al ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Restored hydrologic conditions may be more impactful on plant species composition in some wetland types than others (Johnson et al ). Research from North American grasslands has shown increased species sensitivity to rainfall amounts in drier areas compared to wet areas (Cleland et al ).…”
Section: Discussionmentioning
confidence: 99%
“…One may restore a completely inappropriate hydrologic regime for the given wetland type, yet still have survival and growth of planted species due to their broad hydrologic niche. Restored hydrologic conditions may be more impactful on plant species composition in some wetland types than others (Johnson et al 2014). Research from North American grasslands has shown increased species sensitivity to rainfall amounts in drier areas compared to wet areas (Cleland et al 2013).…”
Section: Wetlandmentioning
confidence: 99%